Design of Advanced Controllers for Speed Control of DC Motor - Arshad Habib Malik; Feroza Arshad; Aftab Ahmad Memon (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
In this research work, an open-loop experimental DC motor from National Instruments is investigated for speed control applications in the nuclear industry with higher accuracy. For performance analysis, the DC motor is mathematically modeled, and advanced control techniques are established. The two design approaches are therefore hardware in loop which is an experimental facility and mathematical in nature which is a simulation model. An adequate mathematical model of the DC motor is developed using the first principle. The hardware realization is accomplished by the DC motor experimental setup. Different advanced control algorithms such as PID, SMC, and MPC are developed for both model-based and hardware-based DC motor research studies. Model development, control synthesis, simulation, and analysis are carried out in Simulink and LabVIEW programming environments. Closed loop performance analyses of nonlinear and predictive controllers are evaluated and found much better, smoother, and robust than linear controllers for speed control of DC motors under different conditions.